Monopoly Intermediary and Information Transmission - Quesada, Lucía (2002)
In this paper we extend Lizzeri’s simple model of information transmission through certification intermediaries. A seller with no means to signal his quality has the possibility to be certified by an institution that owns a technology to discover the true quality and can credibly commit to a disclosure rule. We study the incentives of this institution to disclose information to the buyers. When buyers are risk neutral, the intermediary cannot help to increase the total surplus and, therefore, there is no disclosure of information at equilibrium. Moreover, there always exists an equilibrium with no revelation of information. However, with an unrestricted space of contracts, self selection of sellers indirectly transmits some information. On the other hand, when buyers are risk averse, the intermediary can increase total surplus by inducing better risk sharing. We show that the equilibrium is to offer a menu of contracts where information will be fully disclosed for all types above a certain threshold and no announcement is made for the others.